Usulan Strategi Pemasaran Untuk Meningkatkan Brand Awareness Kedai Kita Aja - Zidane, Axel Rafi; Hartati, Sri (Management Department, Faculty of Economics and Business, Universitas Jambi, 2024)
Kedai Kita Aja faces challenges in increasing brand awareness in the local market, particularly due to limited utilization of social media and a large number of competitors. These issues hinder business growth despite the café offering high-quality products, responsive service, and a comfortable atmosphere. This research proposes a more effective marketing strategy as an effort to attract more customers, enhance competitiveness, and increase brand awareness. The research methodology uses a mixed-method approach, with a questionnaire involving 82 respondents to quantitatively measure brand awareness, as well as qualitative analysis to explore the 4Ps (Product, Price, Place, Promotion) and SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). The findings show that external factors, such as opportunities in social media and threats from competitors, as well as internal factors, such as product strengths and weaknesses in entertainment and financial management, influence the proposed strategy. By implementing this strategy, Kedai Kita Aja is expected to increase brand awareness, strengthen customer loyalty, and improve its competitive position.